Plasmonic Nanoantennas for Photochemistry and Photocatalysis - Chumpol, Kamonpan (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Localised surface plasmon resonances (LSPRs) of sub-wavelength metallic nanoantennas can greatly improve light-matter interactions at the nanoscale beyond the optical diffraction limit and holds great promise for applications ranging from plasmonic photocatalysis to biosensing. Although these applications exploit LSPR-related energy transfer, understanding physical and chemical mechanisms of the LSPR-related energy transfer remains elusive and often relies on complex experimental setups. In this thesis, physical and chemical mechanisms for LSPR-related energy transfer from Al and Au nanoantennas at the single nanoantenna level were investigated using novel methods based on electron beam irradiation and Raman spectroscopy. LSPR-related energy transfer from Al nanoantennas was observed by investigating the volume of a photosensitive probe - polymethylmethacrylate (PMMA) - decomposed in the enhanced electric fields of the metal. By applying the Beer-Lambert law, one possible mechanism associating with energy transfer from Al nanoantennas is two-photon absorption. The chemical transformations in PMMA involved conversion from polymeric properties to graphitic properties as observed in Raman fingerprints. Further investigation of LSPR-related energy transfer was also carried out on Au nanoantennas. In this case, the LSPR was observed to contribute to the catalytic growth of Ge on Au nanostructures. The formation of Ge nanocrystals from diphenylgermane was evident on Au nanoantennas where plasmonic hotspots were present. These two findings have shown great promise for fabricating metal-semiconductor hybrid materials where semiconductor nano-emitters are placed exactly at locations with high electric field intensities, which can thereafter contribute to increasing performance in various applications such as photocatalysis, biosensing, plasmon‐enhanced spectroscopy, and photovoltaic devices. To further investigate the locations of plasmonic hotspots at the single nanoantenna level, an analyte ‐ negative-tone PMMA ‐ was selectively deposited at specific locations corresponding to different electric near-field intensities around Al bowtie nanoantennas. An enhancement factor of (0.55 ± 0.11) × 10^3 was observed to originate from the gaps of the antennas, which is associated with the near-field maxima. Although Al was previously recognised as an inferior plasmonic metal compared to Ag and Au, in this thesis, by engineering Al nanoantennas with rigorous periodic conditions, we observed ultra-narrow resonance linewidths (Q-factor ~150) in addition to multi-plasmon resonances in the visible region of the spectrum for rigid substrate-bound Al bowtie nanoantennas. The findings suggested that the Al platform can potentially be exploited for surface-enhanced Raman spectroscopy and sensing applications, towards cost-effective, sustainable, and large-scale production.
APPROVED
Keywords: Plasmonics, photochemistry, photocatalysis, aluminium nanoantennas, nanophotonics